Migrants and citizens : demographic change in the European state system - Koslowski, Rey (Cornell University Press, 2000)
The Berlin Wall falls as thousands of East Germans move to the West; after the Iron Curtain lifts, West Europeans brace for mass migrations from Eastern Europe; millions of refugees flee Iraq, Bosnia, Haiti, Rwanda, and other strife-torn nations. The ...
Keywords: Europe -- Emigration and immigration.; Europe -- Emigration and immigration -- Government policy.; Europe -- Émigration et immigration.; Europe -- Émigration et immigration -- Politique gouvernementale.; SOCIAL SCIENCE -- Emigration & Immigration.; Emigration and immigration; Emigration and immigration -- Government policy; Europe; Migratie (demografie); Migratiebeleid.; Overheidsbeleid.